INTEGRATION OF ESG PRINCIPLES AND ISLAMIC FINANCE: A SYSTEMATIC LITERATURE REVIEW FROM AN ISLAMIC ECONOMIC PERSPECTIVE - Firyal Mandasari (PT. Samudra Solusi Profesional, 2024)
The growing global emphasis on Environmental, Social, and Governance (ESG) principles has significantly reshaped the landscape of sustainable finance. Parallel to this development, Islamic finance has long promoted ethical, socially responsible, and sustainability-oriented financial practices rooted in Sharia principles. Despite the conceptual convergence between ESG and Islamic finance, the extent and nature of their integration remain fragmented within academic and policy-oriented discussions, particularly in emerging Islamic economies. This study aims to systematically review existing literature on the integration of ESG principles and Islamic finance from an Islamic economic perspective. This article adopts a qualitative research design using a systematic literature review approach. Secondary data were collected from peer-reviewed international and national journals, institutional reports, and policy documents related to ESG, Islamic finance, and sustainable development. The literature was selected using predefined inclusion criteria and analyzed through thematic analysis to identify dominant themes, conceptual linkages, implementation challenges, and future research directions. The findings indicate a strong normative alignment between ESG principles and Islamic finance, particularly in areas such as environmental stewardship (khalifah), social justice (adl), and ethical governance (amanah). However, the review also reveals practical gaps in operationalization, measurement standards, and regulatory harmonization, especially in developing countries like Indonesia. Institutional readiness, ESG disclosure practices, and limited integration frameworks remain key challenges. This study contributes to the Islamic economics literature by synthesizing fragmented insights into a comprehensive conceptual framework linking ESG and Islamic finance. Practically, the findings offer implications for policymakers, Islamic financial institutions, and regulators seeking to strengthen sustainable finance initiatives. The article concludes by proposing strategic directions to enhance the integration of ESG principles within the Islamic finance ecosystem.